Hubungan dan pemikiran para perwira Batak pada masa Revolusi hingga Liberal tahun 1945-1959 - Rafida Dwikaneta; Humaidi Humaidi; Sri Martini (Universitas Negeri Malang, 2023)
This research uses historical method with descriptive-narrative approach and aim to describe the history of the relationship between Batak officers in the Indonesian military during the Revolution to the Liberals in 1945—1959. The results showed that Batak officers were involved in many conflicts, especially in the 1950s, which Ulf Sundhaussen called the Trial and Trial Era. The conflict between the Batak officers involved various events, including the ReRa Hatta incident, the 17 October 1952 incident, Nasution became the Army Chief of Staff for the second time, the Lubis incident, and finally the PRRI rebellion. Differences in educational and religious backgrounds did not really matter to the Batak officers at that time. That means, the Batak officers at that time showed that they prioritized their idealism over their fellow tribesmen. In fact, Batak customs are closely related to the family contained. However, many Batak officers who became leaders in the Army showed that they had a work ethic and morals, in accordance with traditions.Penelitian ini menggunakan metode historis dengan pendekatan deskriptif-naratif yang bertujuan untuk mendeskripsikan sejarah hubungan dan pemikiran para perwira Batak dalam militer Indonesia pada masa Revolusi hingga Liberal tahun 1945—1959. Hasil penelitian menunjukkan bahwa para perwira Batak banyak terlibat konflik, terutama pada tahun 1950-an, yang disebut Ulf Sundhaussen sebagai Era Coba-Coba. Konflik para perwira Batak ini meliputi berbagai peristiwa, antara lain ReRa Hatta, Peristiwa 17 Oktober 1952, Nasution menjadi KSAD kedua kalinya, Peristiwa Lubis, hingga puncaknya pada pemberontakan PRRI. Perbedaan latar belakang pendidikan maupun agama tidak terlalu menjadi masalah bagi para perwira Batak masa itu. Itu artinya, perwira Batak masa itu menunjukkan mengutamakan idealismenya dibandingkan kekerabatan sesama sukunya. Padahal, adat Batak terkenal dengan kekeluargaan yang erat. Bagaimanapun, perwira Batak banyak yang menjadi pemimpin dalam Angkatan Darat menunjukkan bahwa mereka memiliki etos kerja dan moral, sesuai dengan ajaran adatnya.